Upaya UNICEF dalam Aksesibilitas Memperoleh Pendidikan Anak-anak Indonesia di Masa Pandemi Covid-19 - Aldela, Shenika; Priadarsini, Ni Wayan Rainy; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
Accessibility in obtaining education is a right for every child. However, the disruption of the Covid-19 pandemic has made the education system turn into Distance Learning. Meanwhile, the education situation in Indonesia faces various challenges in accessing Distance Learning, specifically access to the internet, technology or infrastructure and the readiness of students or educators. The digital divide between regions in Indonesia is also widening. Children who are in marginalized areas, namely Frontier, Outermost, and Disadvantaged (3T) lose their right to education. Seeing this situation, UNICEF as an IGO has a focus on advocacy for children's rights and has helped the Indonesian government in overcoming the negative impacts on children in the 3T area. The purpose of this qualitative research is to look at the stages of UNICEF's support on advocating for children's rights in access to education during the Covid-19 pandemic. Through analysis of intraorganizational and interorganizational processes, this research looks at how organizations interact and act on this issue. Therefore, UNICEF plays a strategic role and has a focus on generating evidence, implementing programs, working closely with the Government of Indonesia, UN Agencies, private and public sectors. Also, conducting monitoring and evaluation. UNICEF ensures distance learning is accessible for all children and reduces digital gap between regions of Indonesia.